Caso de estudio: propuesta de un plan estratégico de una peluquería y spa en el mercado peruano - García Benites, Sebastián (2023)
The objective of this work is to analyze the company José Antonio Salón & Spa, which provides beauty and relaxation services. This work is developed in six chapters, where strategies will be analyzed and proposed to help the company consolidate itself in the Peruvian market. In chapter I, a situational analysis of the company is carried out that will allow us to understand its origin and direction. In chapters II and III it will be analyzed internally and externally through tools such as PESTE analysis, Porter's five forces, the value chain and the EFE and EFI matrices. In chapter IV and V, strategies are developed through matrices such as SWOT, MPC, PEYEA, BCG, MIE, MCPE, in addition to proposing a new vision and mission, strategic objectives and corporate, business and functional strategies. Finally, in chapter VI, the objectives are controlled through a control map and a comprehensive scorecard (balanced scorecard), with the purpose of relating the strategic objectives to the proposed goals through indicators.